Implementasi Komunikasi Pemasaran Terpadu untuk Peningkatan Brand Awareness UMKM Draw Coffee - Santi Rimadias; Shalsa Bella Putri Irawan; Adinda Pambayun Indraswari; Shandy Surya Lazuardy; Maulana Fadhil; Seichant Mardhira (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia's economy, but often find it difficult to adapt to the demands of marketing in the digital era. This community service aims to increase the marketing effectiveness of Draw Coffee MSMEs, a "ready-to-eat coffee" business based in Jakarta, by applying The Integrated Marketing Communications (IMC) concept. Its main goals include increasing brand awareness, expanding market reach, and building customer loyalty through a combination of digital and traditional marketing channels. The program uses methods such as SWOT analysis, market trend evaluation, and IMC strategies involving social media, digital marketing, and sales promotion. Over the course of three months, the program resulted in an 18% increase in sales, a 30% growth in social media engagement, and a 15% increase in new customers. Despite its success, challenges such as fierce market competition and the need for product diversification are still areas that need to be further developed.